Assessment of Changes in the Hemoglobin Level under the Influence of Comprehensive Spa Therapy Using Therapeutic Radon-Sulfur Waters and Its Correlation with Free Radical Reactions. (21st July 2020) - Kuciel-Lewandowska, Jadwiga; Kasperczak, Michał; Paprocka-Borowicz, Małgorzata
Abstract : Introduction . Hemoglobin is a protein present in erythrocytes of higher organisms. Its main function is to transport oxygen from the lungs to tissues and carbon dioxide from tissues to the lungs. Hemoglobin contains Fe 2+, catalyzes free radical reactions, and may initiate oxidation reactions by enzymatic and nonenzymatic degradation. The aim of the study was to evaluate the effect of balneophysiotherapy on the hemoglobin level in osteoarthritis patients and to try to assess the association of those metabolic changes with free radical reactions. Materials and Methods . The study was conducted in Przerzeczyn-Zdrój spa resort. It included patients receiving spa treatment over 21-day sessions. The studied group consisted of n  = 122 patients with joint and back pain due to osteoarthritis or disc herniation. Their age ranged between 32 and 67 years with a mean age of 53.5. Blood samples were collected before treatment and after 21 days at the spa. Standard tests were used. The results were statistically analyzed using the sign test and the Wilcoxon test. Results . In the study group, we observed a drop in the hemoglobin level following spa treatment. Before treatment, the mean hemoglobin level was 14.1549 g%, and after treatment, it was 14.0008 g%. Conclusions . (1) In the study, we concluded that balneophysiotherapy in osteoarthritis patients resulted in a decrease in the mean hemoglobin level. (2) The decrease in the mean hemoglobin level in osteoarthritis patients treated at the spa resort may indicate an association with free radical reactions. This trial was registered with NCT03405350 .